Infrared vein visualization devices for ease of intravenous access in children: hope versus hype - Vyas, Varuna; Sharma, Ankur; Goyal, Shilpa; Kothari, Nikhil (Anestezjologia Intensywna Terapia, 2021)
Peripheral intravenous placement can be difficult in children. Vein finder devices are vascular access devices that delineate veins lying in the subcutaneous tissues to identify potential venipuncture sites. In this narrative review, we highlight the currently available literature on this device to analyse the hope that this device has to offer vs. the unnecessary hype. The search of the databases (Cochrane Library, Google Scholar, and PubMed) was limited to studies on the paediatric population and in English language between 2011 and 2019. Twenty-three relevant articles were found. Most of the articles did not demonstrate a major impact of these modalities in the general paediatric population. However, they may be beneficial in children with difficult intravenous access. Appropriate simulator mannequins should be utilised to train healthcare providers in using these vein finder devices.